COVID-19 VACCINE DURING PREGNANCY RESULTS OF TRANSPLACENTAL ANTIBODY TRANSFER TO INFANTS AND THROUGH BREAST MILK: A LITERATURE REVIEW - Zahra, Larasati Az (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: This comprehensive literature review investigates the outcomes of administering the BNT162B2 COVID-19 vaccine during pregnancy, focusing on transmitting antibodies through both the placenta and breast milk to infants. The study evaluates existing research findings to provide a nuanced understanding of the immunological implications for newborns born to vaccinated mothers. Methods: This literature review employed the PICO method to develop the review question, focusing on studies published between 2020 and 2023, identified through PubMed, Google Scholar, ScienceDirect, and Scopus using specific keywords related to antibody transfer, COVID-19 vaccine, neonatal immunity, and pregnancy. Result: Nine articles met the inclusion criteria. The review found that COVID-19 vaccination during pregnancy promoted transplacental antibody transfer to infants and the presence of antibodies in breast milk. Conclusion: The results of this study of the literature show that administering the mRNA vaccination in the latter half or third of pregnancy boosts IgA along with IgG levels through transplacental transmission or breastfeeding. BNT162b2 vaccination of mothers in the second trimester is recommended. Breastfeeding has advantages, but limited evidence suggests significant SARS-CoV-2 antibody transfer postpartum. Prospective mothers are urged to vaccinate pre-delivery and consider breastfeeding for antibody transfer.